A study on animal bites and envenomings in rural Varanasi: a community based cross-sectional study - Purwar, Neeti; Kumari, Kalpana; Singh, Anshu; Nagesh, Seetha R. (International Journal Of Community Medicine And Public Health, 2018)
Background: Animal bites are major public health issues in children and adults worldwide. The most important bites are by dogs, cats and monkeys that may cause rabies. Globally, approximately 60,000 annual deaths occur from rabies. Another important bite is by snakes. In India, approximately 94,000–1,25,000 deaths occur by snake bites annually. Therefore, we undertook this study to estimate the incidence of animal bites and to determine the treatment seeking behaviour of victims of animal bites. Methods: It is a cross-sectional study conducted in Bariyasanpur village of Chiraigaon block of Varanasi district. A total of 2039 individuals above one year of age were covered by surveying 342 households out of 437 households. Pre-tested structured schedule was used to find out the incidence of animal bites/ envenomings and treatment seeking behaviour among study subjects during the last one year. Results: The incidence of animal bites/envenomings for the study population in the past one year was 35.31/1000 population. Proportion of the bites by dogs was 51.4% (37/72) followed by scorpions 23.6% (17/72), rats 11.1% (8/72), snakes 11.1% (8/72), monkeys 1.4% (1/72) and jackals 1.4% (1/72). Immediately after the bites, 28 subjects (38.9%) went to faith healers. Only 70.8% took treatment for animal bites at appropriate health facility. Conclusions: From this study, we found a high incidence of dog bite cases and poor treatment seeking behaviour. Probably poor awareness about the animal bites/envenomings could be the main reason for improper management practices. It is a matter of concern for policy planners.